Effects of attackers and attacks on availability requirement in vehicular network: A survey - Sumra, I.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
Availability is one of the key security requirements in vehicular network. The purpose of vehicular network is to serve the user with its potential applications, but this purpose is to fulfill only when networks are available to the end users. Due to open nature of wireless medium, the attackers can affect the vehicular environment. In this paper, we are providing a survey on the attackers and all possible attacks on the availability requirement of vehicular network. The main aim of this study is to describe the threat levels of all possible attacks on the availability. It has been investigated that each level has its own priorities. Threats levels and its priorities will be useful to understand the behavior of attackers and attacks in the vehicular network. Â© 2014 IEEE.